Наукова діяльність відділу природної флори НБС ім. М.М. Гришка НАН України за 65 років його існування - Melnik, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Scientific activities of Natural Flora Department of M.M. Gryshko National Botanical Gardens of National Academy of Sciences of Ukraine are elucidated in historical foreshortening. Achievements of Department in plant introduction, phytogeography and ex situ protection of floristic diversity for 65 years of its existence are considered. Contribution to science of notable botanists and young researchers are estimated. Modern state of scientific researchs is described and new perspectives of these researches are contemplated.